13C methodologies for quantifying biochar stability in soil: A critique. (24th May 2022) - Chalk, Phillip; Smith, Christopher J.
Abstract: Methodologies based on 13 C‐enrichment ( E ), 13 C‐depletion ( D ) and 13 C‐natural abundance ( NA ) to estimate the stability of biochar in soil were critically examined. The stability of 13 C‐enriched biochar can be estimated by the quantitative recovery of excess 13 C, either in the soil or in evolved CO2 . Both approaches have advantages and disadvantages. Recovery in the soil is a measure of both residual biochar 13 C + 13 C immobilised in soil organic matter during biochar decomposition. Variable proportions of organic‐ and inorganic‐C are present in alkaline biochars, and few data exist on the uniformity of labelling, which is a basic requirement of the respired 13 CO2 and E methodology. The E technique has had limited application due to the cost and difficulty of obtaining a uniformly‐enriched feedstock through continuous labelling of plants with 13 CO2 at a constant 13 C enrichment. In contrast, the NA technique has been widely applied. The NA and D techniques are in situ methods that involve the addition of C4 ‐derived biochar to a C3 ‐soil or vice versa. Stability is estimated by a two‐end‐member mixing model that allows the proportion of evolved CO2 derived from the biochar (Cdfb) to be estimated. The mixing model has recently been misused to estimate the Cdfb of 13 C‐enriched biochar, with 13 C‐abundance expressed as erroneously large δ values. 13 C‐based methods provide a yardstick against which rapid stability tests should be evaluated. While numerous laboratory incubation comparisons have been conducted, very few field‐based data have been published. Highlights: 13 C methods for estimating biochar stability are based on uniform isotopic labelling. Organic and inorganic constituents of biochar may not be uniformly labelled. Expression of 13 C enriched biochar as large δ values (>500 units) rather than atom fraction excess led to larger errors in stability estimation. Few 13 C field‐based estimates of biochar stability exist.